2015
DOI: 10.1103/physreva.92.050702
|View full text |Cite
|
Sign up to set email alerts
|

Failure of hydrogenation in protecting polycyclic aromatic hydrocarbons from fragmentation

Abstract: A recent study of soft X-ray absorption in native and hydrogenated coronene cations, C 24 H + 12+m m = 0-7, led to the conclusion that additional hydrogen atoms protect (interstellar) Polycyclic Aromatic Hydrocarbon (PAH) molecules from fragmentation [Reitsma et al., Phys. Rev. Lett. 113, 053002 (2014)]. The present experiment with collisions between fast (30-200 eV) He atoms and pyrene (C 16 H + 10+m , m = 0, 6, and 16) and simulations without reference to the excitation method suggests the opposite. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 40 publications
7
62
0
Order By: Relevance
“…Our experimental results are consistent with density functional theory calculations of the dissociation energies of these ions which have been reported by Gatchell et al (2015). Based on the laser pulse energy dependence, the total energy deposited in photo-absorption events leading to backbone fragmentation of C 16 H + 10+m is 8.17 eV (3 × 2.73 eV), 5.77 eV (2 × 2.88 eV), and 2.95 eV for m = 0, 6, and 16, respectively.…”
Section: Laser Pulse Energy Dependencesupporting
confidence: 92%
“…Our experimental results are consistent with density functional theory calculations of the dissociation energies of these ions which have been reported by Gatchell et al (2015). Based on the laser pulse energy dependence, the total energy deposited in photo-absorption events leading to backbone fragmentation of C 16 H + 10+m is 8.17 eV (3 × 2.73 eV), 5.77 eV (2 × 2.88 eV), and 2.95 eV for m = 0, 6, and 16, respectively.…”
Section: Laser Pulse Energy Dependencesupporting
confidence: 92%
“…Attachment of small numbers of H atoms to coronene cations can for instance quench photoionization-induced H loss from a C 24 H + 12 precursor cation (Reitsma et al 2014(Reitsma et al , 2015. For superhydrogenation of neutral pyrene molecules, an opposite effect was observed.The C-backbone is weakened and fragmentation upon ion collisions or photoionization is increased (Wolf et al 2016;Gatchell et al 2015). Attachment of a single H atom to a PAH radical cations has a dramatic influence on its IR spectrum (Knorke et al 2009) and substantially decreases the HOMO-LUMO gap (Pathak & Sarre 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, for superhydrogenated neutral pyrene molecules, a weakening effect was observed. Here, fragmentation involving C-backbone rupture was found to be the highest decay channel, both in collision and in photoionization studies (Gatchell et al 2015;Wolf et al 2016). For coronene, Reitsma et al (2014) have shown that the attachment of multiple hydrogen atoms to the cation strongly influences the molecular response upon core ionization by soft X-rays, whereas the coronene radical cation [C 24 H 12 ] + undergoes predominantly H-and H 2 -loss, leading to underhydrogenated species, for superhydrogenated species C H n…”
Section: Resultsmentioning
confidence: 85%